ANTI-NEUROPATHIC PAIN ACTIVITY OF THE BANDOTAN (AGERATUM CONYZOIDES L.) LEAVES ACTIVE COMPONENTS, AND THE MECHANISM OF ACTION WITH SAFETY STUDY - Purwandi Sukmawan, Yedy
Neuropathic pain is a condition caused by a lesion or disease of the somatosensory system. The global prevalence of neuropathic pain is 2.6-11%. This condition could impair the quality of life. The use of drugs such as pregabalin, gabapentin, and carbamazepine for neuropathic pain was proven to increase the quality of life of the patients. However, the adverse effects of sedation, orthostatic hypotension, falling, and hypersensitivity could be life-threatening. In addition, many neuropathic pain patients are unsatisfied with the recent drugs treatment. Ageratum conyzoides is a plant that has been demonstrated in preclinical and empirical settings as an analgesic. However, the anti-neuropathic pain activity of this plant is still unknown. The study aim was to determine anti-neuropathic pain activity the mechanism of action as well as the safety profile of the active components of Ageratum conyzoides leaves. The research was initiated by separating of the essential oil component and nonessential oil component (distillation residue) through water-steam distillation. The non-essential oil component was extracted through maceration using 96% ethanol as a solvent. Both components were tested for hyperalgesia and allodynia in animals induced by Chronic Constriction Injury (CCI). The CCI method was selected due to the resemblance to the neuropathic pain condition in the sciatic nerve of humans. The animals were divided into seven groups, namely normal, sham, negative, positive (pregabalin 1.08 mg/kg bw), the group treated with essential oil component (100 mg/kg bw), the group receiving non-essential oil component (100 mg/kg bw), and the group pretreated with naloxone (0.01 mg/kg bw) prior to essential oil component or non-essential oil component. This was then followed by the determination of composition of the most active anti-neuropathic pain component. The three major components were tested for anti-neuropathic pain activity. The components that showed the most potent anti-neuropathic pain activity were then subjected to studies on the synergistic effect with combination with pregabalin and the mechanism of action. The mechanism of action studies were opioid receptor activation, involvement of ATP-sensitive potassium channel, and the change in gamma-aminobutyric acid (GABA) concentration. The opioid receptor activation was tested by observation of naloxone effect, ATP-sensitive potassium channel involvement was studied by intrathecal administration of glibenclamide, and GABA concentration change was determined using ELISA from the L4-L6 spinal cord tissue. The component with the most potent anti-neuropathic pain activity was the tested for acute and sub-chronic toxicities. The essential oil component of Ageratum conyzoides leaves showed a significant difference in anti-neuropathic pain activity compared to the negative group (p<0.05) and the non-essential oil components (p<0.05), but there was no significant difference compared with pregabalin. The GC-MS analysis of the essential oil component indicated the presence of the 60 compounds, with the three major compounds namely precocene II (21.09%), longifolene (9.94%), and caryophyllene (3.64%). The anti-neuropathic pain study showed longifolene (9.94 mg/kg bw) and caryophyllene (3.64 mg/kg bw) had this activity, but not for prekosen II (21.09 mg/kg bw). The result of the combination with pregabalin showed that all the test compounds gave an increased effect compared to pregabalin monotherapy. In additon, mechanism of action study showed that the longifolene involved the activation of the opioid receptor. Meanwhile, the essential oil and kariofilen involved all three mechanisms of action. Although the essential oil and kariofilen had the same mechanism of action, however, the essential oil component significantly increased GABA concentration compared to kariofilen (p<0.05). Based on this results, toxicity tests were carried out on the essential oil. Acute toxicity study revealed the levels of LD50 of 1247.88 mg/kg bw and 1674.57 mg/kg BW for female and male animals, respectively. This level of LD50 fall into the category of mild toxicity. The sub-chronic toxicity test for 28 days did not result in any death. The toxic sign observed was retching, which appeared soon after the essential oil administration and waned five minutes later. In the evaluation of body weight, there was no significant difference compared to the control group. Meanwhile, observations of organ to weight rasio (liver, heart, lungs, spleen, kidneys), biochemical parameters and general hematology did not reveal significant differences, except for the decreased weight of kidney, increased creatinine, decreased hemoglobin level, erythrocyte and hematocrit in male rats. The results of this study could be a basis for research on the development of neuropathic pain alternative treatment using essential oil from Ageratum conyzoides leaves.